2015
DOI: 10.7326/m15-1192
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning Hospital Room Surfaces to Prevent Health Care–Associated Infections

Abstract: The cleaning of hard surfaces in hospital rooms is critical for reducing health care–associated infections. This review describes the evidence examining current methods of cleaning, disinfecting, and monitoring cleanliness of patient rooms, as well as contextual factors that may affect implementation and effectiveness. Key informants were interviewed, and a systematic search for publications since 1990 was done with the use of several bibliographic and gray literature resources. Studies examining surface conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 99 publications
(95 reference statements)
3
133
0
5
Order By: Relevance
“…However, to our knowledge, no multicentre randomised assessment of enhanced terminal room disinfection strategies has been done. 9 We designed the Benefits of Enhanced Terminal Room Disinfection study to assess the effects of four different strategies for terminal room disinfection on acquisition of multidrug-resistant organisms and C difficile .…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, no multicentre randomised assessment of enhanced terminal room disinfection strategies has been done. 9 We designed the Benefits of Enhanced Terminal Room Disinfection study to assess the effects of four different strategies for terminal room disinfection on acquisition of multidrug-resistant organisms and C difficile .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Staphylococcus spp. constitute an important part of the microbiota colonizing the hospital environment [38]. This is apparent even after routine daily cleaning or after adding copper to surfaces that are frequently touched in hospital settings [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…The variable used to measure the impact of cleaning is the concentration of MRSA in the nares of the susceptible patient and the HCW, which better reflects potential health outcomes than environmental levels [11]. Risk of colonization and risk of infection were not calculated because the dose-response function for infection arising from dermal exposure to S. aureus assumes occlusion of the inoculation site for a week, which is not reasonable [36, 37]; and the risk of colonization has only been associated with airborne concentrations of S. aureus [22].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, each HCW provides high-intensity care to a small number of patients [10]. Two surface cleaning interventions were studied: whole room surface cleaning and disinfection and wipe cleaning of touched surfaces [11]. Whole room cleaning is typically performed by environmental service workers, and while the frequency is not standardized, this activity was assumed to occur daily.…”
Section: Introductionmentioning
confidence: 99%